Application of an advanced spatiotemporal model for PM2.5 prediction in Jiangsu Province, China. (May 2020) - Zhang, Ting; Liu, Penghui; Sun, Xue; Zhang, Can; Wang, Meng; Xu, Jia; Pu, Shengyan; Huang, Lei
Abstract: Either long- or short-term of fine particle (PM2.5 ) exposure is associated with adverse health effects especially for children. Primary school students spend much time in schools whereas PM2.5 prediction for such fine-scale places remains a demanding task, let alone a combined prediction with high temporal resolution. The study aimed to estimate PM2.5 levels of different time scales for primary schools in Jiangsu Province, China. Hourly PM2.5 measurements within the academic year (Sept. 2016–June 2017) were collected from 72 routine monitoring sites. Together with PM2.5 emission inventory and dozens of geographic variables, an advanced spatiotemporal land use regression (LUR) model was employed to estimate PM2.5 concentrations of biweekly, seasonal and academic year levels in Jiangsu Province at 2457 primary school locations. 10-fold cross-validation verified high prediction ability with squared correlations R C V 2 of 0.72 for temporal and 0.71 for spatial changes. PM2.5 levels in primary schools in Nanjing and Nantong were >10% higher than that of the corresponding cities while pollution levels in primary schools in Xuzhou were >20% lower. For 10 out of the 13 cities in Jiangsu, PM2.5 levels for primary schools surpassed 70 μg/m 3 in winter. Schools in Lianyungang, Zhenjiang and Huai'an suffered the most. This study demonstrated the fine-scale prediction ability of the novel spatiotemporal LUR model, as well as the potential and necessity to apply it in epidemiological studies. It also verified the emergency of pollution control for primary schools from cities such as Lianyungang and Zhenjiang. Highlights: The model predicts PM2.5 concentrations with high spatiotemporal resolutions. PM2.5 difference between primary schools and monitoring sites could reach 20%. PM2.5 levels in primary schools all exceeded 35 μg/m 3 in Jiangsu. Primary schools from north Jiangsu suffered the most from PM2.5 pollution.